Modulation of Autophagy by Sorafenib: Effects on Treatment Response - Prieto-Domínguez, Nestor; Ordóñez, Raquel; Fernández, Anna; García-Palomo, Andres; Muntané, Jordi; González-Gallego, Javier; Mauriz, José L. (Frontiers in Pharmacology, 2016)
The multikinase inhibitor sorafenib is, at present, the only drug approved for the treatment of hepatocellular carcinoma (HCC), one of the most lethal types of cancer worldwide. However, the increase in the number of sorafenib tumor resistant cells reduces efficiency. A better knowledge of the intracellular mechanism of the drug leading to reduced cell survival could help to improve the benefits of sorafenib therapy. Autophagy is a bulk cellular degradation process activated in a broad range of stress situations, which allows cells to degrade misfolded proteins or dysfunctional organelles. This cellular route can induce survival or death, and depending on cell status and media signals. Sorafenib, alone or in combination with other drugs is able to induce autophagy, but cell response to the drug depends on the complex integrative crosstalk of different intracellular signals. In cancerous cells, autophagy can be regulated by different cellular pathways (Akt-related mammalian target of rapamycin (mTOR) inhibition, 5' AMP-activated protein kinase (AMPK) induction, dissociation of B-cell lymphoma 2 (Bcl-2) family proteins from Beclin-1), or effects of some miRNAs. Inhibition of mTOR signaling by sorafenib and diminished interaction between Beclin-1 and myeloid cell leukemia 1 (Mcl-1) have been related to induction of autophagy in HCC. Furthermore, changes in some miRNAs, such as miR-30, are able to modulate autophagy and modify sensitivity in sorafenib-resistant cells. However, although AMPK phosphorylation by sorafenib seems to play a role in the antiproliferative action of the drug, it does not relate with modulation of autophagy. In this review, we present an updated overview of the effects of sorafenib on autophagy and its related activation pathways, analyzing in detail the involvement of autophagy on sorafenib sensitivity and resistance.